Reported exposure to trauma among adult patients referred for psychological services at the Free State Psychiatric Complex, Bloemfontein - Laurisa van Zyl; Carla Nel; Martie du Toit; Gina Joubert (AOSIS, 2017)
Background: Information regarding lifetime exposure to potentially traumatic events is critical in the management of various psychiatric disorders. Recent South African research suggests high levels of trauma exposure in the general population, however, the prevalence and type of potentially traumatic events among tertiary psychiatric patients are unknown. Objective: The study aimed to explore and describe the extent and nature of reported potentially traumatic events and associated variables in adult patients referred for psychological services at the Free State Psychiatric Complex (FSPC), Bloemfontein. Methods: In this cross-sectional study, demographic information, diagnostic morbidity and co-morbidity, and presence and type of reported trauma exposure reported by patients during the initial assessment were obtained from files of adult patients seen during a one-year period (2010) at the out-patient unit and the in-patient affective ward at the FSPC. Data were captured on data record forms by the researchers and analysed by means of descriptive statistics, univariate analysis and logistic regression (SAS version 9.1). Results: Of the 192 adults (71.9% White and 67.2% female) referred for psychological services,75.5% were diagnosed with mood disorders, 17.2% with anxiety disorders, 22.4% with substance-related disorders and 20.9% with cluster B personality disorders or traits. A total of 145 (75.5%) reported past trauma exposure. The most frequently reported types of trauma exposure were traumatic death/injury of a loved one (37.0%), physical assault (24.5%), witnessed/threatened violence (19.3%), and sexual assault (17.7%). Women were more likely to have been exposed to trauma than men (OR 4.02, 95% CI 1.87-8.62), in particular to traumatic death of a loved one (OR 3.13), physical assault (OR 4.08), or sexual assault (OR 5.43). Conclusions: The findings of this study contribute to current data regarding the prevalence of exposure to trauma and its possible association with mental illness. The importance of comprehensive trauma exposure screening in routine psychiatric interviewing practices is highlighted.